Gambling: The Social-Economic Impact Of Sports Betting On Ugandan Youth; The Case Of Mbale Youth - Masaba, Ayub Kutosi (Universiti Sains Malaysia, 2016)

(untitled)
Worldwide, there is a tremendous increase in the level of gambling activity for example approximatley 70% of Australians participated in some form of gambling in 2009" (Australian Productivity Commission Report on Gambling 2010) and that two out of every three Americans place a bet every year (Jones, 2004). According to Basham and White (2002) “heightened public awareness and participation in gambling has sparked considerable debate about its economic viability and its overall effect on society”. This may explain why some countries are now legalizing gambling with an objective of balancing budget deficits and creating a safe betting gambling environment.